(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aims to enhance specialized features in public transportation to better serve senior citizens and to examine how current transportation systems impact their mobility and daily lives. As older adults often require additional assistance, the study focuses on key concerns, namely, availability, accessibility, safety, and comfort. Based on the findings, the research proposes the development of designated areas and improved services within public transport systems to ensure that senior citizens experience a more secure, convenient, and dignified mode of travel. This study adopts a qualitative research approach, employing survey questionnaires to identify the challenges and experiences of senior citizens about key aspects of public transportation. To gain deeper insights, individual interviews will be conducted to capture personal narratives and gather detailed recommendations, which will inform the development of a more accessible, safe, and senior-friendly public transport system. The findings of the study underscore significant aspects of public transportation as experienced by senior citizens, with mean ratings showing agreement on key factors: availability (2.90), seat and area safety (2.93), accessibility (2.79), and comfort (3.00). While these ratings indicate a moderate level of satisfaction, they also point to persistent challenges that hinder ease of mobility for the elderly. In response to these concerns, the study proposes the development of a specialized area within public transportation systems tailored specifically to the needs of senior citizens. This initiative aims to enhance their commuting experience by prioritizing comfort, safety, accessibility, and overall care. The recommendations emphasize the need to implement targeted improvements based on the survey results, ensuring a more inclusive, supportive, and user-friendly transportation environment for the aging population. This study underscores the vital importance of enhancing designated areas in public transportation to better serve the needs of senior citizens. As one of the most vulnerable sectors of society, elderly individuals face increased risks of discomfort, stress, falls, and injury when public transit systems lack adequate support. Ensuring safety, accessibility, availability, and comfort is not only a matter of convenience but a fundamental aspect of promoting dignity and independence among older adults. By implementing the proposed recommendations such as specialized seating, improved access features, and prioritized services, transport providers can create an inclusive environment where senior citizens feel respected, secure, and empowered to travel confidently, whether accompanied or alone.